Hermeneutical Analysis of Folk Performance Arts in The Special Region of Yogyakarta as a Texts - Pradoko, A.M. Susilo; Kuswarsantyo, Kuswarsantyo; Handayani, Astuti (Universitas Negeri Medan, 2025)
This study discusses folk performing arts in the Special Region of Yogyakarta (DIY) as a cultural text with a focus on the formation of performance, social values, and economic impacts. Arts such as Wayang Topeng, Tayub, Jathilan, and Srandul were chosen because of their role in strengthening cultural identity and the sustainability of social values in society. The study aims to understand performing arts as an aesthetic medium and socio-economic function. Qualitative methods based on ethnography and hermeneutics were used, with direct observation in five regions of the Special Region of Yogyakarta. In-depth interviews were conducted with artists and communities supporting the arts. Data were also obtained from related documents. Hermeneutic analysis highlights performing arts as a representation of aesthetic values and social functions related to the local context. The results of the study show that folk art has a role in social rituals, such as Wayang Topeng to ward off disaster, and Tayub in the Bersih Desa tradition. In addition, this art supports the local economy, creates jobs, and increases tourism. In conclusion, DIY folk performing arts not only function as entertainment, but also as a social and economic driver for the community, so it is important to preserve them.